EVOLUSI FUNGSI AKUNTANSI BERBASIS MODEL VALUES DRIVEN ACCOUNTING - Amerieska, Siti (LP2M Institut Teknologi dan Bisnis Asia Malang, 2016)
This study aimed to determine changes in accounting functions, especially accounting management to follow the development of business and how to model driven value accounting can be applied in making business decisions. The result is a model driven accounting values, are outlined in the three main focuses in the formation of value;, which focuses on improving market returns, focusing on improving performance, and an increase in the first kualitas.Model to increase market returns experienced a shift in accounting functions that can not only make a profit market but also provide value on economic profit more relevant in making business decisions. Improved performance as the second model which has a focus on how business decisions are based on value creation in the Customer, Employee and shareholders. While the third model which contributed to the improvement of quality is based on the business process.